Wildblood : a novel - Blackwood, Lauren (2023)
Kidnapped at six and sent to work at the Exotic Lands Touring Company as a Wildblood tour guide, eighteen-year-old Victoria takes on a dangerous expedition through the monster-filled Jamaican jungle to secure a better future and find where she truly belongs.
Ages 13-18.
Keywords: Fantasy; Magic -- Fiction; Ability -- Fiction; Jamaica -- Fiction; Fantasy fiction; Novels